Lingkungan Bahasa Arab di Pemondokan Santri Mahasiswa Pondok Pesantren Mambaus Sholihin - Makinuddin, Mohammad (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2016)
There have been a number of factors shaping and deter-mining the success of learning and mastering foreign langua-ges, including Arabic language. Along with learning activities to achieve excellent ability in comprehending Arabic language, language environment becomes another most essential factor. The existence of Arabic environment (bÃ®âah lughawÃ®yah Ê»ArabÃ®yah) beco-mes an exceptionally pivotal because it brings about what so-called âcontextual learning activityâ around the students. The article discusses the case of Mambaus Sholihin Islamic Boarding School which develops such language environment. The study shows that this Islamic educational institution has faced, however, several problems regarding inconsistent implementation of the language environment even though there have been numerous language instructors graduated from a number of universities in the Middle East and Indonesia as well as Islamic boarding schools in Indonesia. Specifically, these are a number of problems as regards to the issue: 1) there has been no such an organizing team; 2) the students have no self-confidence to practice Arabic; 3) the human resources engaging in the implementation of the Arabic environ-ment have less motivation to earnestly run it; 4) bad influence of senior students to the new students; and 5) there has been no strong awareness to use Arabic for daily communication.